Metastatic Urothelial Carcinoma from Transplanted Kidney with Complete Response to an Immune Checkpoint Inhibitor - Ryan S. Chiang; Ashton A. Connor; Brant A. Inman; Wen-Chi Foo; David N. Howell; John F. Madden; Matthew J. Ellis; Aparna S. Rege; Michael R. Harrison (Case Reports in Urology)
Background. Donor-derived malignancy is a rare complication in patients who undergo organ transplant. Approaches to treatment have largely been individualized based on clinical circumstances given the lack of evidence-based guidelines, with therapeutic options ranging from discontinuation of immunosuppression and transplantectomy to the addition of chemotherapy or radiotherapy. Case Presentation. Herein, we describe a 60-year-old woman with metastatic donor-derived upper tract urothelial carcinoma (UTUC) discovered nine years postrenal transplant. Molecular diagnostic studies using polymerase chain reaction amplification of short tandem repeat alleles and HLA tissue typing proved that the urothelial carcinoma originated from donor tissue. She achieved sustained complete remission with transplant nephroureterectomy, retroperitoneal lymphadenectomy, immunosuppression withdrawal, and immunotherapy with pembrolizumab. Routine radiologic surveillance has demonstrated 15-month progression-free survival to date off pembrolizumab, and she is now under consideration for retransplantation. Conclusions. Immunotherapy using checkpoint inhibitors can serve as a novel treatment option for patients in the clinical predicament of having a solid organ transplant and simultaneous metastatic malignancy. In this report, we also discuss the oncogenic potential of BK virus, the use of checkpoint inhibitors in urothelial carcinoma, and the feasibility of retransplant for this patient population.